2019
DOI: 10.1155/2019/7065713
|View full text |Cite
|
Sign up to set email alerts
|

Value of Infrared Thermography Camera Attached to a Smartphone for Evaluation and Follow-up of Patients with Graves’ Ophthalmopathy

Abstract: Purpose. Graves’ ophthalmopathy (GO) is the most common extra-thyroid manifestation of Graves’ disease (GD). The Clinical Activity Score (CAS) has been widely used to evaluate GO inflammation severity and response to treatment; however, it is quite subjective. Infrared thermography (IRT) is a portable and low-cost device to evaluate local temperature and assess inflammation. The aim was to evaluate ocular temperature by IRT as an instrument for measuring inflammatory activity in GO and its correlation with CAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
(27 reference statements)
0
9
0
1
Order By: Relevance
“…Klamann et al 25 used thermography to examine eyes with bacterial corneal ulcers and showed a positive correlation between clinical observations of signs related to ocular surface inflammation and OST findings. Minatel Riguetto et al 26 used infrared thermography to evaluate OST in patients with thyroid orbitopathy, and found a good correlation between the patients' Clinical Activity Score and their OST.…”
Section: Discussionmentioning
confidence: 99%
“…Klamann et al 25 used thermography to examine eyes with bacterial corneal ulcers and showed a positive correlation between clinical observations of signs related to ocular surface inflammation and OST findings. Minatel Riguetto et al 26 used infrared thermography to evaluate OST in patients with thyroid orbitopathy, and found a good correlation between the patients' Clinical Activity Score and their OST.…”
Section: Discussionmentioning
confidence: 99%
“…In general, IR-TICs connected to smartphones provide accurate temperature measurements and their use in medicine for diagnostic purposes is also recently documented [33][34][35]. They have been used to evaluate post-surgical wounds, tumor lesions assessment, skin inflammation related to pathologies, and ophtalmopathies.…”
Section: Discussionmentioning
confidence: 99%
“…They have been used to evaluate post-surgical wounds, tumor lesions assessment, skin inflammation related to pathologies, and ophtalmopathies. The IR-TIC used for this study has features comparable to IR-TICs used in other medical studies [26,27,29,31,[33][34][35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Об увеличении ТГП на фоне глазных воспалительных процессов, за исключением ЗС, ранее сообщалось в различных исследованиях [13,16]. Сложности в диагностике ЗС могут возникнуть вследствие недостаточного опыта, субклинического течения воспаления или атипичности симптомов.…”
Section: Discussionunclassified